USING MICROSOFT ACCESS IN PREPARATION PROGRAMS IN RETAIL SALES (CASE STUDY IN GRAHA INTERIOR INDAH) - Lie Liana (Jurnal Ilmiah Dinamika Teknik, 2011)
Microsoft Access as one of database processor can help to create a database application in a relatively short time, so this application is used to create a sales program in Interior Graha Indah. Sales program created is still very simple with all its limitations, but expected to be used to assist the sales process. This sales program is a beginner program and is expected to be developed further in the future. Keywords: Microsoft Access, sales prog